Really modern issues for masters from World German Cloud University - Nadia Ivanivna Shiyan; Rainer Unland; Martin Gröger; Dietrich Brandt; Torsten Brinda; Vardan Surenovich Mkrttchian (Academy of Cognitive and Natural Sciences, 2014)
The study aims to identify opportunities for masters who gives World German Cloud University. The article describes the entire process of project implementation on the example of one popular specialty Industrial Engineering and Management (IEM). Our goal is to create and foster relationships between students of different countries and support them in their personal and professional development. Our network consists of 68 local groups in 26 countries, currently to 50,000 students. Project open wishing to join can contact a representative World German Cloud University in Ukraine - Professor Nadia Shiyan.